Photoacoustic imaging of lamina cribrosa microcapillaries in porcine eyes - Pramanik, Manojit (2018)
Due to the embedded nature of the lamina cribrosa (LC) microcapillary network, conventional imaging techniques have failed to obtain the high-resolution images needed to assess the perfusion state of the LC. In this study, both optical resolution (OR) and acoustic resolution (AR) photoacoustic microscopy (PAM) techniques were used to obtain static and dynamic information about LC perfusion in ex vivo porcine eyes. The OR-PAM system could resolve a perfused LC microcapillary network with a lateral resolution of 4.2 μm and also provided good depth information (33 μm axial resolution) to visualize through-thickness vascular variations. The AR-PAM system was capable of detecting time-dependent perfusion variations. This study represents the first step towards using an emerging imaging modality (PAM) to study the LC’s perfusion, which could be a basis for further investigation of the hemodynamic aspects of glaucomatous optic neuropathy.